Progress in Serum Metabolomics Research on Venous Thromboembolic Diseases - Liu, Qiao; Zhang, Qiang; Shi, Shuming; Rong, Jianjie (Journal of Contemporary Medical Practice, 2025)
Venous thromboembolic disease (VTE), comprising deep vein thrombosis (DVT) and pulmonary embolism (PE), exhibits rising incidence and mortality rates due to the lack of early, sensitive, and specific diagnostic biomarkers. Serum metabolomics, a branch of metabolomics, focuses on studying the dynamic changes of all small-molecule metabolites in serum. In recent years, numerous researchers have identified serum differential metabolites associated with VTE development through serum metabolomics studies in VTE patients. By investigating their metabolic pathways, these studies suggest that the pathogenesis may be linked to abnormalities in lipid metabolism, amino acid metabolism, energy metabolism, and adenosine metabolism. Serum metabolomics has revealed key metabolic abnormalities in VTE progression, offering new perspectives for early diagnosis, mechanism elucidation, and targeted therapy. However, its clinical application still faces numerous challenges.